A clinical study of various cutaneous manifestations in neonates - Usmani, Shams Zia; Saxena, Kshitij; Koti, Venkatarao; Bhatnagar, Shrish; Paliwal, Gaurav; Yadav, Shivani; Singh, Anukriti (International Journal of Research in Dermatology, 2019)
Background: Cutaneous manifestations are common in neonates. Transient and pathological neonatal dermatoses should be differentiated to avoid unnecessary treatment and thus considering the variable nature and severity of neonatal skin lesions, it is important to be aware of the transient skin lesions in newborn and to differentiate these from other serious conditions which will avoid unnecessary therapy to the neonates and the parents can be assured of good prognosis of these skin manifestations. The present study has been carried out to study the clinical pattern of cutaneous lesion in neonatal period. Methods: A total of 255 neonates from Department of Dermatology in collaboration of Department of Pediatrics, Era’s Lucknow Medical College and Hospital were evaluated for cutaneous manifestations. A detailed assessment regarding history, clinical examination and investigations were recorded and analyzed. Results: Out of 255 neonates, 138 (54.1%) were males and 117 (45.9%) were females. The sex ratio (M:F) was 1.18. The most common dermatoses were physiological desquamation (54.1%) and mongolian spots (37.6%) followed by milia (19.6%), miliaria (14%), epstein pearls (10.2%). Conclusions: The physiological and transient cutaneous lesions are common are in neonates. Physiological cutaneous manifestations were quite frequent apart from birthmarks/congenital cutaneous manifestations. An understanding of these manifestations helps in managing and deciding the appropriate manifestation.